State Enterprises : What Remains? - Kikeri, Sunita; Kolo, Aishetu (World Bank, Washington, DC, 2012)
After two decades of privatization, has government ownership and control of enterprises declined substantially? A rigorous assessment is difficult in the absence of systematic data on state enterprises. But ongoing research suggests that while privatization has helped reduce the state's role in some developing countries and regions, in most others the stock of state enterprises remains relatively large. State enterprises continue to play a major role in many developing regions and, in some sectors, across more or less all of them.